EXPLORING THEMATIC DEPTH IN THE SHORT STORY, ‘THE LAST QUESTION’ BY ISSAC ASSIMOV: EMPLOYING LANGUAGE FUNCTIONS - Aiman Imran; Shaukat Ali; Muhammad Ishfaq; Nizar Ali; Wajid Ullah (International Journal of Contemporary Issues in Social Sciences, 2024)
Human language is essential for communication, which enables the expression of thoughts, prediction, reference, and societal interactions, in order to make it inseparable from communication itself. The purpose of the study is to identify functions of language in Short Story The Last Question by Issac assimov and reveal the thematic depth of the story to engage readers. It further highlights the exemplary contributions of the linguists like Geoffrey Leech, Ludwig Karl Buhler and Michael Halliday to enhance our understanding of litrary functions of language. For achieving the aforementioned objectives, the researchers apply Roman Jakobson’s model of language functions to analyze the short story and compare it with previous studies. The findings highlights six functions of language—referential, emotive, conative, phatic, metalingual, and poetic—and their role in communication. The study emphasizes how these functions convey information, express emotions, influence behavior, establish connections, clarify language, and enhance aesthetic experience in the narrative. The findings of this research will be helpful for the readers in general to know the functions of language and for the researchers in specific as it will provide insights for further research.